Comparison of indoor contact time data in Zambia and Western Cape, South Africa suggests targeting of interventions to reduce Mycobacterium tuberculosis transmission should be informed by local data. Issue 1 (December 2015) - McCreesh, Nicky; Looker, Clare; Dodd, Peter; Plumb, Ian; Shanaube, Kwame; Muyoyeta, Monde; Godfrey-Faussett, Peter; Corbett, Elizabeth; Ayles, Helen; White, Richard
Abstract Background In high incidence settings, the majority ofMycobacterium tuberculosis (M.tb ) transmission occurs outside the household. Little is known about where people's indoor contacts occur outside the household, and how this differs between different settings. We estimate the number of contact hours that occur between adults and adult/youths and children in different building types in urban areas in Western Cape, South Africa, and Zambia. Methods Data were collected from 3206 adults using a cross-sectional survey, on buildings visited in a 24-h period, including building function, visit duration, and number of adults/youths and children (5–12 years) present. The mean numbers of contact hours per day by building function were calculated. Results Adults in Western Cape were more likely to visit workplaces, and less likely to visit shops and churches than adults in Zambia. Adults in Western Cape spent longer per visit in other homes and workplaces than adults in Zambia. More adults/youths were present at visits to shops and churches in Western Cape than in Zambia, and fewer at homes and hairdressers. More children were present at visits to shops in Western Cape than in Zambia, and fewer at schools and hairdressers. Overall numbers of adult/youth indoor contact hours were the same at both sites (35.4 and 37.6 h in Western Cape and Zambia respectively, p  = 0.4). Child contact hours were higher in Zambia (16.0 vs 13.7 h, p  = 0.03). Adult/youth and child contact hours were highest in workplaces in Western Cape and churches in Zambia. Compared to Zambia, adult contact hours in Western Cape were higher in workplaces (15.2 vs 8.0 h, p  = 0.004), and lower in churches (3.7 vs 8.6 h, p  = 0.002). Child contact hours were higher in other peoples' homes (2.8 vs 1.6 h, p  = 0.03) and workplaces (4.9 vs 2.1 h, p  = 0.003), and lower in churches (2.5 vs 6.2, p  = 0.004) and schools (0.4 vs 1.5, p  = 0.01). Conclusions Patterns of indoor contact between adults and adults/youths and children differ between different sites in highM.tb incidence areas. Targeting public buildings with interventions to reduceM.tb transmission (e.g. increasing ventilation or UV irradiation) should be informed by local data.